HIV-1 RNA may decline more slowly in semen than in blood following initiation of efavirenz-based antiretroviral therapy. - Graham, S; Holte, SE; Dragavon, J; Ramko, K; Mandaliya, K; McClelland, R; Peshu, N; Sanders, E; Krieger, J; Coombs, R (2012)
OBJECTIVES: Antiretroviral therapy (ART) decreases HIV-1 RNA levels in semen and reduces sexual transmission from HIV-1-infected men. Our objective was to study the time course and magnitude of seminal HIV-1 RNA decay after initiation of efavirenz-based ART among 13 antiretroviral-naïve Kenyan men. METHODS: HIV-1 RNA was quantified (lower limit of detection, 120 copies/mL) in blood and semen at baseline and over the first month of ART. Median log(10) HIV-1 RNA was compared at each time-point using Wilcoxon Signed Rank tests. Perelson's two-phase viral decay model and nonlinear random effects were used to compare decay rates in blood and semen. RESULTS: Median baseline HIV-1 RNA was 4.40 log(10) copies/mL in blood (range, 3.20-5.08 log(10) copies/mL) and 3.69 log(10) copies/mL in semen (range, <2.08-4.90 log(10) copies/mL). The median reduction in HIV-1 RNA by day 28 was 1.90 log(10) copies/mL in blood (range, 0.56-2.68 log(10) copies/mL) and 1.36 log(10) copies/mL in semen (range, 0-2.66 log(10) copies/mL). ART led to a decrease from baseline by day 7 in blood and day 14 in semen (p = 0.005 and p = 0.006, respectively). The initial modeled decay rate was slower in semen than in blood (p = 0.06). There was no difference in second-phase decay rates between blood and semen. CONCLUSIONS: Efavirenz-based ART reduced HIV-1 RNA levels more slowly in semen than in blood. Although this difference was of borderline significance in this small study, our observations suggest that there is suboptimal suppression of seminal HIV-1 RNA for some men in the early weeks of treatment.